2015
DOI: 10.1016/j.healun.2014.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Systolic blood pressure on discharge after left ventricular assist device insertion is associated with subsequent stroke

Abstract: Background Stroke is a significant complication in patients supported with continuous-flow left ventricular assist devices (CF-LVAD) and hypertension (HTN) is a significant risk factor for stroke, but the association between blood pressure and stroke in LVAD patients is not well characterized. Methods We identified 275 consecutive patients who survived implant hospitalization between 1/2005 and 4/2013. Patients were divided into above and below median SBP (100 mmHg) groups based on their averaged systolic bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 16 publications
0
51
0
Order By: Relevance
“…A high blood pressure in this case might rather be an indicator of sustained damage to already fragile cerebral arterioles from chronically elevated blood pressure not only preceding but also following LVAD implantation. Investigators at Washington University have recently reported that a systolic blood pressure above the mean (>100 mmHg) 48 h before discharge from the hospital after implantation was associated with a higher risk of ischemic and hemorrhagic stroke, a mean of 16 months later without a clear difference by device type [25••]. Otherwise, strokes may also reflect a systemic process leading to hemorrhage that is independent of the cerebral vasculature.…”
Section: Hypertension and Stroke In Left Ventricular Assist Devicesmentioning
confidence: 99%
“…A high blood pressure in this case might rather be an indicator of sustained damage to already fragile cerebral arterioles from chronically elevated blood pressure not only preceding but also following LVAD implantation. Investigators at Washington University have recently reported that a systolic blood pressure above the mean (>100 mmHg) 48 h before discharge from the hospital after implantation was associated with a higher risk of ischemic and hemorrhagic stroke, a mean of 16 months later without a clear difference by device type [25••]. Otherwise, strokes may also reflect a systemic process leading to hemorrhage that is independent of the cerebral vasculature.…”
Section: Hypertension and Stroke In Left Ventricular Assist Devicesmentioning
confidence: 99%
“…Additionally, strict blood pressure control is increasingly recognized as a therapeutic goal to reduce the rates of hemorrhagic and embolic stroke (20,21). Will a more focused effort on blood pressure control also improve pulsatility, thereby preventing both GI bleeding and the development of aortic insufficiency?…”
mentioning
confidence: 99%
“…Etiology of stroke after LVAD implantation seems equally distributed between embolic and hemorrhagic strokes . Multiple risk factors for stroke occurrence after LVAD implantation have been documented, including history of stroke, pre‐existing atrial fibrillation, diabetes mellitus, suboptimal anticoagulation regimens, hypertension, systemic infection, and aortic cross‐clamping with cardioplegic arrest . Regardless of etiology, postoperative stroke is an important cause of morbidity after LVAD implantation and can be a cause for hospital readmissions .…”
Section: Discussionmentioning
confidence: 99%